2007
DOI: 10.1109/tpds.2007.1035
|View full text |Cite
|
Sign up to set email alerts
|

Assisted Peer-to-Peer Search with Partial Indexing

Abstract: Abstract-In the past few years, peer-to-peer (P2P) networks have become a promising paradigm for building a wide variety of distributed systems and applications. The most popular P2P application till today is file sharing, e.g., Gnutella, Kazza, etc. These systems are usually referred to as unstructured, and search in unstructured P2P networks usually involves flooding or random walking. On the other hand, in structured P2P networks (DHTs), search is usually performed by looking up a distributed inverted index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(17 citation statements)
references
References 35 publications
0
14
0
3
Order By: Relevance
“…The works showed that the complexity of the view selection depends on how the query optimizer estimates the size of the view that is considered for materializing. Works discussed in [11] presented a cache management mechanism to identify the materialized views across distributed nodes. The query is communicated in the network connecting various nodes until a node where materialization is available is found.…”
Section: Background and Preliminariesmentioning
confidence: 99%
“…The works showed that the complexity of the view selection depends on how the query optimizer estimates the size of the view that is considered for materializing. Works discussed in [11] presented a cache management mechanism to identify the materialized views across distributed nodes. The query is communicated in the network connecting various nodes until a node where materialization is available is found.…”
Section: Background and Preliminariesmentioning
confidence: 99%
“…In attenuated bloom filter technique [9], an index for every neighbor and up to 'd' number of hops is maintained. In Zhang and Hu [10], a global but partial index is built using a Distributed Hash Tables (DHT) built on top of the unstructured overlay. In eSearch [11], index for every term is created.…”
Section: Figure1 An Example P2p Overlay Networkmentioning
confidence: 99%
“…For example, [7] uses latent semantic indexing technique to build up full-text search in structured overlays; [8], [9] combine structured and unstructured overlays to reduce search cost. Different from these works, we consider multiple-keyword search in structured networks.…”
Section: Introductionmentioning
confidence: 99%